Doing Family across Borders: The Role of Routine Practices, Traditions and Festivities in Lithuania - Česnuitytė, Vida (Vilnius University Open Series, 2020)
The chapter present results of research which objective is to identify family practices which mobilise the members of a personal network of Lithuanian residents into a family irrespective of the (non-) existence of blood or marriage relations and the members’ place of residence (in Lithuania or abroad). Hypotheses formulated in the survey were tested against the data of the quantitative representative sociological survey (the fieldwork was carried out in June-July 2018), and the data of quota survey (the fieldwork was carried out in August-September 2018). Both surveys were conducted in Lithuania while implementing the scientific research project ‘Global Migration and Lithuanian Family: Family Practices, Circulation of Care and Return Strategies’. The research results show that the emigration of a family member makes a personal network more open to individuals not related to them by blood or marriage. At the same time, the members of the family of procreation are less frequent participants in the practices of the daily routine, joint holidays, birthdays or New Year’s Eve celebrations, and that causes danger to the stability of the family or personal network and even to its survival. Though, participation at religious festivities and the Mother and Father’s Day celebrations still remain the practices which strengthens personal and family relationships of emigrant’s members.